Caring for patients with early COPD: How hazardous is to family carers' psychological health? - Figueiredo, Daniela (2013)
Evidence shows that providing care to a family member with advanced COPD can be stressful. Much less is known about the perceived difficulties of caring for a patient with early COPD and its impacts on family carers' psychological health. This study aimed to analyse the subjective burden among family carers of patients with early COPD and its association with anxiety and depression. A cross-sectional study with a convenience sample of family carers of patients with early COPD (GOLD 1 and GOLD 2) was conducted. A questionnaire was used to collect socio-demographics. The Hospital Anxiety and Depression Scale (HADS) was used to assess anxiety and depression. Subjective burden was assessed with the Carers' Assessment Difficulties Index (CADI). Descriptive statistics and Spearman correlations were applied. A total of 100 family carers (71% female; 58.2±12.6 years old) have participated. The majority were spouses (64%), caring for ≥ 4 years (56%). 65% of participants presented symptoms of anxiety (HADS-A ≥8), 31% depression (HADS-D≥ 8) and 27% both. The most perceived stressful situations were related to feelings of helplessness/loss of control of the situation (43%), sleep disturbance (41%), financial strain (26%) and emotional well-being affected (25%). CADI global score correlated significantly with anxiety (rs=0.307; p=0.002) and depression (rs=0.295; p=0.003). The findings suggest that, even at early COPD, the caregiving experience can be stressful, with negative impacts on family carers' psychological health. The results underline the relevance of supportive interventions for family carers to be delivered earlier in the COPD course, in order to prevent burden.